New concepts of glucose-induced insulin secretion in the development of type 2 diabetes: clinical implications - Ivan Ivanovich Dedov; Olga Michailovna Smirnova; Kononenko Vladimirovna Irina (Сахарный диабет)
The prevalence of type 2 diabetes is increasing dramatically, and the pathogenesis of the disease has been studied extensively in recent years. Of particular interest, incretins are reported to cause changes in insulin secretion that affect the natural development of the disease. The emergence of new drugs that act via the incretin axis have led many clinicians to consider their place in clinical practice.